PENGARUH GCG DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN KINERJA KEUANGAN SEBAGAI MODERASI (Studi Empiris pada Perusahaan Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2022-2024) - Fajar Arief Rachman; Rico Wijaya; Nyimas Dian Maisyarah (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyse the influence of Good Corporate Governance (GCG) and company size on profit management, with financial performance as the moderating variable, in mining companies listed on the Indonesia Stock Exchange between 2022 and 2024. The study used a quantitative approach with secondary data in the form of company annual reports. The sample was obtained using purposive sampling, resulting in 57 companies with a total of 171 observation data. Data analysis was performed using Structural Equation Modelling (SEM) based on Partial Least Squares (PLS) with the help of WarpPLS 7.0. The results of the study show that good corporate governance and company size influence profit management, and financial performance is able to moderate the influence of good corporate governance and company size on profit management.